UV-B PROTECTING ACTIVITY OF SYNECHOCOCCUS SPP. PCC7942 BY ANTIOXIDATIVE DEFENSE SYSTEM - NIDA FATIMA; HERA CHAUDHRY; IFFAT ZAREEN AHMAD (International Journal of Pharma and Bio Sciences, 2015)
Cyanobacteria are the prokaryotes and the most primitive organism to evolve on the earth. They are autotrophs and perform oxygenic mode of photosynthesis. During the course of evolution cyanobacteria were exposed to extreme habitats and environmental conditions which developed an ability to synthesize an array of complex secondary metabolites in these cells. One such class of compounds is UVR protectants which include some photosynthetic pigments, antioxidant compounds and enzymes, mycosporine-like amino acids and scytonemin. Of these, antioxidant enzymes provide an important defense against the harmful effects of UVR. UV-B radiations are deleterious when it comes to human health because in recent times due to depletion of ozone layer more radiations reach the earth’s surface. Therefore, there arises a need for novel and natural UV protectants. Cyanobacteria are suitable candidates for the isolation and purification of such compounds. For this, study should be conducted on the various antioxidant enzymes like SOD, CAT, POD and ASC-POD in cyanobacteria.